Recurrent Pneumothorax in a Pediatric Patient with Crohn’s Disease Receiving Ustekinumab Treatment: Case Report - Marta Freixas Bermejo; Luis Riera Soler; Laura García Martínez; Oscar Segarra Cantón (Case Reports in Gastroenterology)
Introduction: We present the case of a patient with Crohn’s disease who experienced recurrent pneumothorax after starting treatment with ustekinumab. Case Presentation: A patient with Crohn’s disease started an induction regimen with intravenous ustekinumab, and 2 months later he presented a left-sided pneumothorax. It had an atypical evolution that required surgical management. The medication was withdrawn and the pneumothorax resolved completely. One year later, he had a new flare-up of Crohn’s disease and ustekinumab therapy was restarted, presenting a new episode of pneumothorax. Conclusion: To our knowledge, this is the first report of recurrent pneumothorax following two separate attempts to initiate ustekinumab.